Expression of microRNAs in human platelet-poor plasma: analysis of the factors affecting their expression and association with proximal genetic variants. Issue 12 (1st December 2020) - Rodriguez-Rius, Alba; Martinez-Perez, Angel; López, Sonia; Sabater-Lleal, Maria; Souto, Juan Carlos; Soria, José Manuel
ABSTRACT: To translate circulating microRNAs (miRNAs) into the clinic, a deeper understanding of the factors affecting their expression is needed. In this study, we explored the features affecting the expression of miRNAs and their genetic regulation using the expression data of 103 miRNAs obtained by qPCR in the platelet-poor plasma of 104 subjects. The principal components (PCs) of the expression of the miRNAs were associated with technical and biological features (e.g., synthetic controls or sex) and with blood cell counts. Also, the associations with proximal genetics variants were analysed. We found that haemolysis marker (dCt hsa-miR-23a-3p-hsa-miR-451a) was correlated strongly (β = 0.84, p = 2.07x10 −29 ) with the second PC, which explained 10.1% of the overall variability. Thus, we identified haemolysis as a source of variability for miRNA expression even in mild hemolyzed samples (haemolysis marker dCt <5). In addition to hsa-miR-23a-3p and hsa-miR-451a, the miRNAs most stable and most susceptible to haemolysis were identified. Then, we discovered that the expression of miRNAs in platelet-poor plasma was not biased by any blood cell count, and thus, our results supported their role as biomarkers of tissue-specific conditions. Finally, we identified 1, 323 genetic variants that corresponded to 158 miRNA expression quantitative trait loci for 14 miRNAs (FDR <0.2), which were enriched in promoter regions (p = 0.03). This enrichment corresponded to a range of specific tissues (e.g., breast or fat) although not to blood tissue, supporting the concept that the expression of circulating miRNAs is under the genetic control of different tissues.